Development and Fabrication of a Pressure Swing Adsorption System Using Molecular Sieve 13X for Integrated CO₂ Capture and Electrochemical Conversion - Mitra Eviani; Tirto Prakoso; Dadan Kusdiana; Pramujo Widiatmoko; Ida Bagus Oka Lyong Budhatama; Setyo Yanus Sasongko; Aryan Fathoni Amri; Wibawa Hendra Saputera; Hary Devianto (Scientific Contributions Oil and Gas, 2025)
This study focuses on the development and performance evaluation of a Pressure Swing Adsorption (PSA) system utilizing molecular sieve Zeolite 13X for CO2 capture. A fixed-bed reactor was designed and simulated with Aspen Adsorption to optimise adsorption conditions. The system, tested with a 24.75 L/min gas feed (10% CO2, 90% N2) at 30 °C and 6 bar, operated cyclically every 7 minutes. Simulation results recommended a reactor volume of 4.9 L (ID 102 mm × T/T 600 mm). Sensitivity analysis showed that adsorption capacity declined as CO2 concentration increased, with CO2 uptake decreasing from 24.75 L/min at 10%-mol to 8.44 L/min at 70%-mol. Key design parameters such as feed flow rate, intraparticle voids, bulk density, and particle size were also evaluated. A prototype was built based on simulation results and tested, achieving a 120 s breakthrough time and an optimal 60 s swing interval over 17 cycles. This work supports the future integration of PSA-based CO2 capture with electrochemical CO2 reduction (ECO2R).